2018
DOI: 10.1074/jbc.ra118.003036
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor receptor 5 (FGFR5) is a co-receptor for FGFR1 that is up-regulated in beta-cells by cytokine-induced inflammation

Abstract: Fibroblast growth factor receptor-1 (FGFR1) activity at the plasma membrane is tightly controlled by the availability of co-receptors and competing receptor isoforms. We have previously shown that FGFR1 activity in pancreatic beta-cells modulates a wide range of processes, including lipid metabolism, insulin processing, and cell survival. More recently, we have revealed that co-expression of FGFR5, a receptor isoform that lacks a tyrosine-kinase domain, influences FGFR1 responses. We therefore hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Furthermore, the IgSF gene FGFR1 was predicted to be regulated by miRNA novel-294 at 12 hpi (Supplementary Table 3). A previous study found that FGFR1 expression improved beta-cell survival in cytokineinduced inflammation (33). Hence, we speculated that the upregulation of the novel-294 in puppies' livers promotes the immune response of puppies to T. canis infection via increasing the expression of FGFR1.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the IgSF gene FGFR1 was predicted to be regulated by miRNA novel-294 at 12 hpi (Supplementary Table 3). A previous study found that FGFR1 expression improved beta-cell survival in cytokineinduced inflammation (33). Hence, we speculated that the upregulation of the novel-294 in puppies' livers promotes the immune response of puppies to T. canis infection via increasing the expression of FGFR1.…”
Section: Discussionmentioning
confidence: 88%
“…Unlike the other four members, FGFR5 (known as FGFRL1) lacks a tyrosine kinase domain. It plays a role in regulating excessive activation of the FGF-FGFR1 signaling pathway [ 4 , 5 ]. The signaling axis of FGFRs is primarily activated in a ligand-dependent manner, by binding of fibroblast growth factors (FGFs) and the subsequent receptor dimerization induced intracellular kinase transautophosphorylation events [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The human FGFR family comprises five members: FGFR1, FGFR2, FGFR3, FGFR4, and FGFR5. FGFRs 1–4 are receptor tyrosine kinases consisting of an extracellular ligand binding domain and a tyrosine kinase domain, which are expressed on the cell membrane [3]. FGFR fusions and other alterations have been reported in a wide range of solid tumors, including cholangiocarcinoma [4], bladder cancer [5], lung cancer [6], and glioblastoma [7].…”
Section: Introductionmentioning
confidence: 99%